Solids rheology for dehydrated food and biological materials - Telis, VRN; Telis-Romero, J.; Gabas, A. L. (Taylor & Francis Inc, 2005)
Mechanical properties of food products and biological materials are greatly affected by the drying process and are considered one of the most important quality attributes of dehydrated products. The aim of this work was to review theoretical principles and mathematical modeling, analyzing the measurement techniques and major experimental results that exist in the literature about rheological properties of dehydrated foods and biological materials. Different methods of measuring rheological parameters (fundamental and empiric or imitative) are discussed and major experimental results, as well as the rheological models used in their analysis, published in recent years are presented.
Keywords: drying; food; rheological properties; viscoelasticity; texture